Lithium carbon nanotube doped porous carbon, preparation method and application thereof
The preparation of lithium carbon nanotube doped with porous carbon is solved through co-precipitation method and vacuum evaporation method, which solves the problems of conductivity and structural defects of existing porous carbon materials, achieves efficient conductivity and structural stability, and improves lithium-ion batteries performance and cycle life.
Patent Information
- Application Number
- CN202411667697.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-11-21
AI Technical Summary
The poor electronic conductivity, poor compressive resistance and many structural defects of existing porous carbon materials limit their performance in applications with high requirements for high conductivity and first-time efficiency. The existing lithium doping method leads to poor lithium uniformity. , hole capacity and aperture size decrease, affecting battery performance.
The carbon nanotube doped resin precursor is prepared by co-precipitation method, and porous carbon is formed by carbon dioxide activation treatment, and lithium is deposited in carbon nanotube doped porous carbon by vacuum evaporation method to form an efficient conductive network and structural support to enhance the material electronic conductivity and structural stability.
It significantly improves the electronic conductivity and rate performance of the material, optimizes the pore structure, improves the mechanical and thermal stability of the material, enhances the lithium ion conductivity and energy storage capacity, and improves the charge and discharge performance and cycle stability.
Smart Images

Figure CN119160878A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of battery material preparation, in particular to a lithium carbon nanotube doped porous carbon, a preparation method and application thereof. Background Art
[0002] Porous carbon can be used as an energy storage material because of its rich pore structure and good electrical conductivity. It has a wide range of applications in the field of energy storage and is often used to prepare supercapacitors, lithium-ion batteries, lithium-sulfur batteries, sodium-ion batteries, etc. The parameters that affect the performance of porous carbon mainly include specific surface area, pore size, pore volume, mechanical strength and electronic conductivity. At present, the commercial porous carbon materials are mainly prepared from resin-based materials or biomass materials through pre-carbonization, activation and other processes. However, the existing porous carbon materials have the disadvantages of poor electronic conductivity, poor compressive resistance and many structural defects, resulting in low first efficiency, which limits its performance in some applications with high requirements for electrical conductivity and first efficiency. Porous carbon is also often used as a precursor for silicon-carbon materials. At present, the market has higher and higher requirements for the kinetic performance and first efficiency of new silicon-carbon materials, which requires the porous carbon used as the precursor of silicon-carbon materials to have high electronic conductivity and high first efficiency.
[0003] A Chinese patent with an application publication date of August 2, 2024 and an application publication number of CN118419892A discloses a metal-doped porous carbon, silicon-carbon material and a method for preparing the same. The patent improves the electronic conductivity and the first efficiency by doping lithium in the porous carbon; then, by a deposition method, a solid electrolyte is deposited on the outermost layer to improve the first coulombic efficiency and high-temperature storage performance of the material. However, the performance improvement of this method is limited, and it will cause the pore volume and pore size of the material to decrease, thereby reducing the storage capacity and transmission speed of the electrode material for ions. In addition, the lithium doping uniformity in its preparation method is poor, resulting in excessive or low local lithium content, which may cause uneven current distribution and affect the charge and discharge performance of the battery. The preparation process is complicated, which not only increases the production cost and time cost, but also may introduce more uncertain factors, reducing production efficiency and product quality stability. Summary of the invention
[0004] In view of the shortcomings of the prior art, the present invention aims to provide a lithium carbon nanotube-doped porous carbon with high electronic conductivity, few structural defects, and the ability to improve rate performance and first efficiency, a preparation method and its application.
[0005] One of the purposes of the present invention is to provide a method for preparing lithium carbon nanotube-doped porous carbon, the preparation method comprising: Firstly, a carbon nanotube-doped resin precursor is prepared by a coprecipitation method, and then a curing treatment is performed to obtain a carbon nanotube-doped resin; Then, the carbon nanotube-doped resin is activated by using carbon dioxide to obtain carbon nanotube-doped porous carbon; Then, lithium is deposited on the carbon nanotube-doped porous carbon by using a vacuum evaporation method to obtain lithium carbon nanotube-doped porous carbon.
[0006] Preferably, the method for preparing a carbon nanotube-doped resin precursor by coprecipitation method comprises: First, add an aqueous solution of phenolic compounds, then drop an aqueous solution of aldehyde compounds, and then add carbon nanotubes, pore-forming agent and ammonia water in sequence, mix well, react at 50-100° C. for 1-6 hours, and filter to obtain a carbon nanotube-doped resin precursor.
[0007] Preferably, the mass ratio of the phenolic compound, the aldehyde compound, the carbon nanotubes and the pore-forming agent is 100:100-200:1-5:1-5.
[0008] Preferably, the carbon nanotubes include one or more of hydroxylated carbon nanotubes, aminated carbon nanotubes, carboxylated carbon nanotubes or nitrogen-doped carbon nanotubes.
[0009] Preferably, the phenolic compound includes one or more of m-cresol, p-cresol, o-cresol, 3,5-dimethylphenol or resorcinol.
[0010] Preferably, the aldehyde compound includes one or more of formaldehyde, acetaldehyde, furfural or salicylaldehyde.
[0011] Preferably, the pore-forming agent includes one or more of polyvinyl alcohol, polyvinyl pyrrolidone or polyvinyl amine.
[0012] Preferably, the concentration of the phenolic compound aqueous solution is 15-50wt%.
[0013] Preferably, the concentration of the aldehyde compound is 10-40wt%.
[0014] Preferably, the concentration of the ammonia water is 15-20wt%, and the mass ratio of the phenolic compound to the ammonia water is 1:8-12.
[0015] Preferably, the method for curing the carbon nanotube-doped resin precursor comprises: The carbon nanotube-doped resin precursor is cured at 500-800° C. for 1-6 hours to obtain the carbon nanotube-doped resin.
[0016] Preferably, the method for activating the carbon nanotube-doped resin comprises: After the carbon nanotube-doped resin is heated to 1100-1400° C., carbon dioxide is introduced and an activation treatment is performed for 30-300 minutes to obtain carbon nanotube-doped porous carbon.
[0017] Preferably, the flow rate of carbon dioxide for activation treatment is 100-500 ml / min.
[0018] Preferably, the method of depositing lithium on the carbon nanotube-doped porous carbon using vacuum evaporation comprises: Lithium deposition is carried out under vacuum conditions. High-energy laser beam irradiation is used to vaporize lithium and deposit it into the pores and surface of carbon nanotube-doped porous carbon. The evaporation time is 5-15 minutes, and then carbon dioxide is introduced for passivation treatment.
[0019] Preferably, the mass ratio of carbon nanotube-doped porous carbon to lithium is 100:1-5.
[0020] Preferably, the wavelength of the laser beam is 900-1090 nm, the pulse width is 0.5 ms-4 ms, and the laser power is 100 W-600 W.
[0021] Preferably, the flow rate of carbon dioxide for passivation treatment is 100-500 ml / min.
[0022] Preferably, the passivation treatment time is 30-300 min.
[0023] The second object of the present invention is to provide a lithium carbon nanotube-doped porous carbon, wherein the lithium carbon nanotube-doped porous carbon comprises 1-5wt% carbon nanotubes, 1-5wt% lithium carbonate and 90-98wt% porous carbon.
[0024] The third object of the present invention is to provide an application of lithium carbon nanotube-doped porous carbon in the preparation of secondary batteries.
[0025] The beneficial effects of the present invention include: The present invention firstly uniformly dopes carbon nanotubes in a resin precursor, and then prepares carbon nanotube-doped porous carbon through curing and activation. The carbon nanotubes construct an efficient conductive network in the pores and matrix of the porous carbon, which can improve the electronic conductivity of the material, and can provide structural support as a skeleton to enhance the mechanical properties and thermal stability of the material, which is conducive to optimizing the pore structure. Then, metallic lithium vapor is deposited in the pores of the porous carbon by a gas phase method, which can further reduce the defects of the porous carbon, fill the defect sites of the porous carbon, enhance the structural stability of the material, and improve the ionic conductivity of the material, thereby improving the first coulomb efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is the SEM image of the lithium carbon nanotube-doped porous carbon prepared in Example 1. DETAILED DESCRIPTION
[0027] In the following description, certain specific details are included to provide a comprehensive understanding of each disclosed embodiment. However, one skilled in the relevant art will recognize that the embodiments can be implemented without one or more of these specific details and with other methods, components, materials, etc.
[0028] Unless otherwise required herein, the words "include" and "comprising" should be interpreted as having an open and inclusive meaning, ie, "including but not limited to".
[0029] References to "one embodiment" or "an embodiment" or "a preferred embodiment" or "certain embodiments" throughout this specification are intended to include, in at least one embodiment, the specific referenced elements, structures or features described in connection with the embodiment. Thus, the phrases "in one embodiment" or "in an embodiment" or "in a preferred embodiment" or "in certain embodiments" appearing in different places throughout the specification do not necessarily all refer to the same embodiment. Furthermore, the specific elements, structures or features may be combined in any appropriate manner in one or more embodiments.
[0030] According to a first aspect of the present invention, a method for preparing lithium carbon nanotube-doped porous carbon is provided, the preparation method comprising: Firstly, a carbon nanotube-doped resin precursor is prepared by a coprecipitation method, and then a curing treatment is performed to obtain a carbon nanotube-doped resin; Then, the carbon nanotube-doped resin is activated by using carbon dioxide to obtain carbon nanotube-doped porous carbon; Then, lithium is deposited on the carbon nanotube-doped porous carbon by using a vacuum evaporation method to obtain lithium carbon nanotube-doped porous carbon.
[0031] In the present invention, firstly, the carbon nanotubes are doped by coprecipitation method in the reaction process before preparing the resin. The carbon nanotubes have a unique tubular structure and a certain rigidity. In the polymerization process, the surrounding carbonaceous materials will be deposited and polymerized around the carbon nanotubes, and the carbon nanotubes can work together with the monomer molecules. On the one hand, the carbon nanotubes are gradually embedded in the resin structure during the polymerization process, which is conducive to achieving more uniform doping and can better participate in the formation process of the resin; on the other hand, the functional groups on the surface of the carbon nanotubes may form a strong interaction with the active groups in the resin molecules, making the carbon nanotubes less likely to fall off during the subsequent treatment process, which is conducive to maintaining the structural stability of the material; on the third hand, the carbon nanotubes can be used as a structural template to guide the direction of polymerization, and the structure formed around the carbon nanotubes will be retained in the subsequent activation treatment process, so that the pores of the porous carbon present the shape and distribution characteristics related to the carbon nanotubes, forming a more ordered pore structure; on the fourth hand, the carbon nanotubes can also be used as a skeleton to provide structural support to enhance the mechanical properties and thermal stability of the material.
[0032] Furthermore, when lithium is deposited, on the one hand, a more stable and ordered pore structure is conducive to the uniform deposition of lithium, and the doping of carbon nanotubes also provides more active sites for lithium deposition; on the other hand, the deposition of lithium can fill some defect sites in the porous carbon, reduce defects in the material, and make the material structure more complete and stable; on the third hand, metallic lithium has high ionic conductivity. After depositing it in porous carbon, it provides more channels and active sites for the transmission of ions. Lithium ions can migrate more quickly at the interface between lithium and porous carbon, thereby significantly improving the ionic conductivity of the material; at the same time, the structure of carbon nanotube-doped porous carbon provides good support and constraint for the deposition of lithium, which can prevent lithium from agglomerating and changing in volume during the charge and discharge process.
[0033] In a preferred embodiment of the present invention, the method for preparing a carbon nanotube-doped resin precursor by coprecipitation method comprises: First, add an aqueous solution of phenolic compounds, then drop an aqueous solution of aldehyde compounds, and then add carbon nanotubes, pore-forming agent and ammonia water in sequence, mix well, react at 50-100° C. for 1-6 hours, and filter to obtain a carbon nanotube-doped resin precursor.
[0034] In the present invention, after adding phenolic compounds, aldehyde compounds, carbon nanotubes, pore-forming agent and ammonia water, the phenolic compounds and aldehyde compounds react to generate a phenolic resin precursor, the pore-forming agent is used to promote the formation of pores, and the carbon nanotubes are uniformly doped in the phenolic resin precursor during the reaction.
[0035] In the present invention, the reaction temperature is, for example, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C or 100°C, and any value therebetween. The reaction time is, for example, 1h, 2h, 3h, 4h, 5h or 6h, and any value therebetween.
[0036] In the present invention, if the temperature is lower than 50°C, on the one hand, the polycondensation reaction of the aldehyde resin proceeds very slowly, which may lead to a significant extension of the reaction time, affecting the production efficiency; on the other hand, the dispersion effect of the carbon nanotubes in the system may deteriorate, because the fluidity of the system is weakened at a lower temperature, which is not conducive to the uniform dispersion of the carbon nanotubes in the resin precursor, and agglomeration may occur, thereby affecting the performance of the material; on the third hand, it will also make it difficult to form an ideal pore structure, resulting in a lower specific surface area and porosity of the material, affecting its adsorption performance and ion transmission capacity, etc.
[0037] In the present invention, if the temperature is higher than 100°C, on the one hand, it may induce side reactions and cause excessive cross-linking of the phenolic resin, and even side reactions such as thermal decomposition, which will destroy the structure of the resin and reduce the performance and stability of the material; on the other hand, too high a temperature may make it difficult to control the size and distribution of the pores, and may even cause the pore structure to collapse, affecting the pore characteristics of the material; on the third hand, it consumes a lot of energy, increases production costs, and also places higher requirements on production equipment. More complex heating and temperature control equipment may be required to ensure temperature stability, increasing the difficulty and risk of production.
[0038] In a preferred embodiment of the present invention, the mass ratio of the phenolic compound, the aldehyde compound, the carbon nanotubes and the pore-forming agent is 100:100-200:1-5:1-5. Taking the mass of the phenolic compound as 100 parts as an example, the mass of the aldehyde compound is, for example, 100 parts, 110 parts, 120 parts, 130 parts, 140 parts, 150 parts, 160 parts, 170 parts, 180 parts, 190 parts or 200 parts, the mass of the carbon nanotubes is, for example, 1 part, 2 parts, 3 parts, 4 parts or 5 parts, the mass of the pore-forming agent is, for example, 1 part, 2 parts, 3 parts, 4 parts or 5 parts, and any point value between the above two parts.
[0039] In a preferred embodiment of the present invention, the carbon nanotubes include one or more of hydroxylated carbon nanotubes, aminated carbon nanotubes, carboxylated carbon nanotubes or nitrogen-doped carbon nanotubes.
[0040] In the present invention, hydroxylated carbon nanotubes, amino carbon nanotubes, carboxylated carbon nanotubes and nitrogen-doped carbon nanotubes can interact with the active groups in the phenolic resin, thereby enhancing the interfacial bonding force between the carbon nanotubes and the phenolic resin and facilitating the uniform dispersion of the carbon nanotubes in the phenolic resin.
[0041] In the present invention, the carbon nanotubes are, for example, hydroxylated carbon nanotubes, aminated carbon nanotubes, amino carbon nanotubes, nitrogen-doped carbon nanotubes, hydroxylated carbon nanotubes and aminated carbon nanotubes, hydroxylated carbon nanotubes and carboxylated carbon nanotubes, carboxylated carbon nanotubes and nitrogen-doped carbon nanotubes, or a combination of carboxylated carbon nanotubes, hydroxylated carbon nanotubes and nitrogen-doped carbon nanotubes.
[0042] Preferably, the carbon nanotubes are carboxylated carbon nanotubes. The presence of carboxylic acid groups makes the carbon nanotubes have good hydrophilicity and can be well dispersed in the aqueous phase system, which is very advantageous for the preparation method of coprecipitation, which is usually carried out in a liquid phase environment. The carboxylated carbon nanotubes can undergo chemical reactions such as esterification reaction with the phenolic hydroxyl groups in the phenolic resin, thereby enhancing the compatibility and bonding between the two.
[0043] Preferably, the phenolic compound includes one or more of m-cresol, p-cresol, o-cresol, 3,5-xylenol or resorcinol. The phenolic compound is, for example, the phenolic compound includes m-cresol, p-cresol, o-cresol, 3,5-xylenol, resorcinol, m-cresol and p-cresol, m-cresol and o-cresol, m-cresol and 3,5-xylenol, m-cresol and resorcinol, m-cresol, p-cresol and o-cresol, or a combination of m-cresol, p-cresol, o-cresol and 3,5-xylenol.
[0044] Preferably, the aldehyde compound includes one or more of formaldehyde, acetaldehyde, furfural or salicylaldehyde, and the aldehyde compound is, for example, formaldehyde, acetaldehyde, furfural, salicylaldehyde, formaldehyde and acetaldehyde, formaldehyde and furfural, formaldehyde and salicylaldehyde, formaldehyde, acetaldehyde and furfural, formaldehyde, acetaldehyde and salicylaldehyde, or a combination of formaldehyde, acetaldehyde, furfural and salicylaldehyde.
[0045] Preferably, the pore-forming agent includes one or more of polyvinyl alcohol, polyvinyl pyrrolidone or polyvinyl amine, and the pore-forming agent is, for example, polyvinyl alcohol, polyvinyl pyrrolidone, polyvinyl amine, polyvinyl alcohol and polyvinyl pyrrolidone, polyvinyl alcohol and polyvinyl amine, or a combination of polyvinyl alcohol, polyvinyl pyrrolidone and polyvinyl amine.
[0046] Preferably, the concentration of the aqueous solution of phenolic compounds is 15-50wt%, for example, 15wt%, 20wt%, 25wt%, 30wt%, 35wt%, 40wt%, 40wt% or 50wt%, and any value therebetween.
[0047] Preferably, the concentration of the aldehyde compound is 10wt%-40wt%, for example, 10wt%, 20wt%, 30wt% or 40wt%, and any value therebetween.
[0048] Preferably, the concentration of the ammonia water is 15-20wt%, for example, 15wt%, 16wt%, 17wt%, 18wt%, 19wt% or 20wt%; the mass ratio of the phenolic compound to the ammonia water is 1:8-12, for example, 1:8, 1:9, 1:10, 1:11 or 1:12.
[0049] In a preferred embodiment of the present invention, the method for curing the carbon nanotube-doped resin precursor comprises: The carbon nanotube-doped resin precursor is cured at 500-800° C. for 1-6 hours to obtain the carbon nanotube-doped resin.
[0050] In the present invention, the temperature of the curing treatment is, for example, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, or 800°C.
[0051] Specifically, the curing treatment is carried out in an inert atmosphere. During the curing treatment at 500-800°C, the carbon nanotube-doped resin precursor undergoes a crosslinking reaction and a preliminary carbonization reaction, and a three-dimensional network structure and a basic pore structure are formed. At the same time, the interface bonding force between the carbon nanotubes and the phenolic resin is further enhanced during the curing process. At the same time, due to the skeleton support of the carbon nanotubes, the volume shrinkage of the material during the crosslinking process can be limited, and the stability of the pore structure can be maintained. When the temperature is lower than 500°C, it may be difficult for the phenolic resin to be fully crosslinked; when the temperature is higher than 800°C, it may cause the resin to decompose or other side reactions to occur.
[0052] In the present invention, the curing treatment time is, for example, 1 h, 2 h, 3 h, 4 h, 5 h or 6 h.
[0053] As the curing time increases, the cross-linking reaction of the phenolic resin becomes more complete and the performance of the material gradually becomes stable. If the curing time is too short, the resin may not be completely cross-linked, resulting in insufficient material performance. If the curing time is too long, energy may be wasted and may cause excessive changes in material properties or side reactions.
[0054] Preferably, the heating rate of the curing treatment is 1-10°C / min, for example, 1°C / min, 2°C / min, 4°C / min, 6°C / min, 8°C / min or 10°C / min.
[0055] In a preferred embodiment of the present invention, the method for activating the carbon nanotube-doped resin comprises: After the carbon nanotube-doped resin is heated to 1100-1400° C., carbon dioxide is introduced and an activation treatment is performed for 30-300 minutes to obtain carbon nanotube-doped porous carbon.
[0056] In the present invention, during the activation treatment process, carbon dioxide etches the porous carbon material, further optimizing the pore structure, increasing the specific surface area and porosity of the material, forming more active sites, and adjusting the size, distribution and shape of the pores by controlling the activation temperature, time and flow rate of carbon dioxide. During the activation process, high temperature treatment makes the contact between the carbon nanotubes and the porous carbon closer, which is more conducive to the transmission of electrons and forms a stronger structural support. The presence of carbon nanotubes can also prevent structural collapse.
[0057] In the present invention, the temperature of the activation treatment is, for example, 1100° C., 1150° C., 1200° C., 1250° C., 1300° C., 1350° C. or 1400° C. Too high a temperature of the activation treatment may cause structural damage or performance degradation of the material.
[0058] In the present invention, the activation treatment time is, for example, 30 min, 50 min, 100 min, 150 min, 200 min, 250 min or 300 min. If the activation time is too short, the carbon material may not be fully etched, resulting in insufficient porosity and specific surface area, while if the activation time is too long, the material may be over-etched, making the structure too loose and reducing the mechanical strength of the material.
[0059] Preferably, the heating rate of the activation treatment is 1-10°C / min, for example, 1°C / min, 2°C / min, 4°C / min, 6°C / min, 8°C / min or 10°C / min.
[0060] Preferably, the flow rate of carbon dioxide for activation treatment is 100-500 ml / min, for example, 100 ml / min, 200 ml / min, 300 ml / min, 400 ml / min or 500 ml / min. In a preferred embodiment of the present invention, the method for depositing lithium on the carbon nanotube-doped porous carbon comprises: Lithium deposition is carried out under vacuum conditions. High-energy laser beam irradiation is used to vaporize lithium and deposit it into the pores and surface of carbon nanotube-doped porous carbon. The evaporation time is 5-15 minutes, and then carbon dioxide is introduced for passivation treatment.
[0061] In the present invention, a high-energy laser beam irradiates a lithium source, causing the lithium to heat up rapidly and vaporize. The vaporized lithium atoms have high activity and fluidity, and can diffuse and deposit more easily into the pores and surface of the carbon nanotube-doped porous carbon. The presence of carbon nanotubes in the porous carbon can provide more deposition sites, and also help to enhance the interaction between lithium and carbon materials. This interaction can enhance the binding force between lithium and carbon materials, and improve the stability and electrochemical performance of the material. Lithium deposition into the pores of porous carbon can increase the energy storage capacity of the material on the one hand, and the pore structure can also limit the volume change of lithium, reduce stress during the charge and discharge process, and improve the cycle stability of the material.
[0062] The evaporation time is, for example, 5 min, 6 min, 7 min, 8 min, 9 min, 10 min, 11 min, 12 min, 13 min, 14 min or 15 min. If the evaporation time is too short, the lithium deposition amount may be insufficient, and the lithium cannot be fully exerted; while if the evaporation time is too long, the lithium may be excessively deposited, making the structure of the material unstable, and even blocking the pores, affecting ion transmission.
[0063] After the carbon dioxide is introduced, it reacts with lithium to form a lithium carbonate passivation layer on the surface of the lithium. This passivation layer can prevent lithium from further reacting with oxygen and moisture in the air, thereby improving the stability and safety of the material.
[0064] Preferably, the mass ratio of carbon nanotube-doped porous carbon to lithium is 100:1-5, for example, 100:1, 100:2, 100:3, 100:4 or 100:5.
[0065] If the mass ratio of carbon nanotube-doped porous carbon to lithium is too large, the content of lithium is relatively too small, and the effect of improving energy storage capacity and conductivity is not obvious; if the mass ratio of carbon nanotube-doped porous carbon to lithium is too small, too much lithium is deposited on the carbon nanotube-doped porous carbon. During the charge and discharge process, the repeated insertion and extraction of lithium will cause a large volume change, which may cause the material structure to be damaged and reduce the material's cycle stability. When the lithium content is too high, lithium agglomeration is also likely to occur in the material, affecting the uniform distribution of lithium in the material, and thus affecting the consistency and reliability of battery performance. The mass ratio of 100:1-5 can achieve a good synergistic effect between carbon nanotube-doped porous carbon and lithium. Within this ratio range, the carbon material can provide sufficient structural support and active sites, and the lithium content can also meet the requirements of energy storage and conductivity.
[0066] Specifically, the carbon nanotube-doped porous carbon is placed in a vacuum chamber and evacuated to a vacuum (≤1 torr), a lithium block is placed in a vapor deposition chamber, a high-energy laser beam is emitted by a laser, and the laser beam is focused and irradiated onto the plating material, the temperature is raised to 300-400°C, and the material is heated and vaporized. The vaporized lithium vapor is deposited in the pores and on the surface of the carbon nanotube-doped porous carbon to obtain lithium carbon nanotube-doped porous carbon.
[0067] Preferably, the wavelength of the laser beam is 900-1090nm, for example 900nm, 930nm, 960nm, 1000nm, 1030nm, 1060nm or 1090nm, the pulse width is 0.5ms-4ms, for example 0.5ms, 1ms, 1.5ms, 2ms, 2.5ms, 3ms, 3.5ms, 4ms, 4.5ms or 5ms, and the laser power is 100W-600W, for example 100W, 200W, 300W, 400W, 500W or 600W.
[0068] Preferably, the flow rate of carbon dioxide for the passivation treatment is 100-500 ml / min, for example, 100 ml / min, 200 ml / min, 300 ml / min, 400 ml / min or 500 ml / min.
[0069] Preferably, the passivation treatment time is 30-300 min, for example, 30 min, 50 min, 100 min, 150 min, 200 min, 250 min or 300 min.
[0070] In a preferred embodiment of the present invention, the preparation method comprises: (1) First, add an aqueous solution of a phenolic compound, then dropwise add an aqueous solution of an aldehyde compound, and then sequentially add carbon nanotubes, a pore-forming agent, and ammonia water, mix well, react at 50-100° C. for 1-6 hours, and filter to obtain a carbon nanotube-doped resin precursor. Under an inert atmosphere, cure the carbon nanotube-doped resin precursor at 500-800° C. for 1-6 hours to obtain a carbon nanotube-doped resin; (2) heating the carbon nanotube-doped resin to 1100-1400° C., introducing carbon dioxide, and performing activation treatment for 30-300 min to obtain carbon nanotube-doped porous carbon; (3) According to the mass ratio of carbon nanotube-doped porous carbon: metallic lithium = 100:1-5, the carbon nanotube-doped porous carbon is placed in a vacuum chamber and evacuated to a vacuum (≤1 torr), and a lithium block is placed in a vapor deposition chamber. A high-energy laser beam is emitted by a laser and focused onto the coating material. The temperature is raised to 300-400°C to cause it to vaporize. The vaporized lithium vapor is deposited in the pores and on the surface of the carbon nanotube-doped porous carbon. The vapor deposition time is 5-15 minutes. Then, carbon dioxide is introduced at normal pressure at a flow rate of 100-500 ml / min for 30-300 minutes to obtain lithium carbon nanotube-doped porous carbon.
[0071] According to a second aspect of the present invention, there is provided a lithium carbon nanotube-doped porous carbon obtained by the preparation method as described in the first aspect, wherein the lithium carbon nanotube-doped porous carbon comprises 1-5wt% carbon nanotubes, 1-5wt% lithium carbonate and 90-98wt% porous carbon.
[0072] The lithium carbon nanotube-doped porous carbon has a high specific surface area and a good pore structure, and has good electrical properties, energy storage capacity and rate performance. At the same time, the stability and cycle life of the material are also greatly improved.
[0073] According to a third aspect of the present invention, there is provided a use of lithium carbon nanotube-doped porous carbon in preparing a secondary battery.
[0074] Preferably, the secondary battery comprises a sodium battery or a lithium battery.
[0075] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0076] Example The present invention is further described in detail below in conjunction with the embodiments. It is to be understood that the specific embodiments described herein are only used to explain the relevant invention, rather than to limit the invention. It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments can be combined with each other.
[0077] In the following examples, unless otherwise specified, all raw materials are commercially available products.
[0078] Example 1 A method for preparing lithium carbon nanotube-doped porous carbon comprises the following steps: (1) 100 g of m-cresol was added to 300 g of deionized water and dispersed evenly, and then 450 g of formaldehyde (30 wt%) solution was added dropwise, and then 3 g of carboxylated carbon nanotubes, 3 g of polyvinyl alcohol and 1000 g of 17% ammonia water were added in sequence and mixed evenly, reacted at 80 ° C for 3 h, and filtered; (2) The obtained filter residue was heated to 650°C in a nitrogen atmosphere at a heating rate of 5°C / min and cured for 3 hours, then heated to 1250°C at a heating rate of 5°C / min and activated by introducing carbon dioxide gas at a flow rate of 300 ml / min for 150 minutes to obtain carbon nanotube-doped porous carbon; (3) 100g of carbon nanotube-doped porous carbon was placed in a vacuum chamber and evacuated to a vacuum level of ≤1 torr. 3g of lithium block was placed in a vapor deposition chamber. A high-energy laser beam was emitted by a laser and focused onto the coating material. The temperature was raised to 350°C to cause it to vaporize. The vaporized lithium vapor was deposited in the pores and on the surface of the carbon nanotube-doped porous carbon. The vapor deposition time was 10min. Then, carbon dioxide was introduced at a flow rate of 300ml / min at normal pressure for 150min for passivation treatment to obtain lithium carbon nanotube-doped porous carbon.
[0079] Example 2 A method for preparing lithium carbon nanotube-doped porous carbon comprises the following steps: (1) 100 g of p-cresol was added to 100 g of deionized water and dispersed evenly, and then 1000 g of acetaldehyde (10 wt%) solution was added dropwise, and then 1 g of carboxylated carbon nanotubes, 1 g of polyvinyl pyrrolidone and 1000 g of 17 wt% ammonia water were added in sequence and mixed evenly, reacted at a temperature of 50 ° C for 6 h, and filtered; (2) The obtained filter residue was heated to 500°C at a heating rate of 1°C / min, cured for 6 hours, and then heated to 1100°C at a heating rate of 1°C / min, and carbon dioxide gas was introduced at a flow rate of 100 ml / min for activation for 300 minutes to obtain carbon nanotube-doped porous carbon; (3) 100g of carbon nanotube-doped porous carbon was placed in a vacuum chamber and evacuated to a vacuum level of ≤1 torr. 1g of lithium block was placed in a vapor deposition chamber. A high-energy laser beam was emitted by a laser and focused onto the coating material. The temperature was raised to 300°C to vaporize the material. The vaporized lithium vapor was deposited in the pores and on the surface of the carbon nanotube-doped porous carbon. The vapor deposition time was 5 min. A carbon dioxide passivation treatment was then carried out at a flow rate of 100 ml / min for 300 min at normal pressure to obtain lithium carbon nanotube-doped porous carbon.
[0080] Example 3 A method for preparing lithium carbon nanotube-doped porous carbon comprises the following steps: (1) 100 g of 3,5-dimethylphenol was added to 500 g of deionized water and dispersed evenly. Then, 500 g of furfural (40 wt%) solution was added dropwise, and then 5 g of carboxylated carbon nanotubes, 5 g of polyethylene amine and 1000 g of 17 wt% ammonia water were added in sequence and mixed evenly. The mixture was reacted at 100 °C for 1 h and filtered. (2) The obtained filter residue was heated to 800°C at a heating rate of 10°C / min, cured for 1 hour, and then heated to 1400°C at a heating rate of 10°C / min, and carbon dioxide gas was introduced at a flow rate of 500 ml / min for activation for 30 minutes to obtain carbon nanotube-doped porous carbon; (3) 100g of carbon nanotube-doped porous carbon was placed in a vacuum chamber and evacuated to a vacuum level of ≤1 torr. 5g of lithium block was placed in a vapor deposition chamber. A high-energy laser beam was emitted by a laser and focused onto the coating material. The temperature was raised to 400°C to vaporize the material. The vaporized lithium vapor was deposited in the pores and on the surface of the carbon nanotube-doped porous carbon. The vapor deposition time was 15min. Then, carbon dioxide was introduced at a flow rate of 500ml / min at normal pressure for 30min to obtain lithium carbon nanotube-doped porous carbon.
[0081] Example 4 The difference from Example 1 is that 0.5 g of carboxylated carbon nanotubes are used in step (1), and the rest is the same as Example 1.
[0082] Example 5 The difference from Example 1 is that 1 g of carboxylated carbon nanotubes is used in step (1), and the rest is the same as Example 1.
[0083] Example 6 The difference from Example 1 is that 5 g of carboxylated carbon nanotubes are used in step (1), and the rest is the same as Example 1.
[0084] Example 7 The difference from Example 1 is that 6 g of carboxylated carbon nanotubes are used in step (1), and the rest is the same as Example 1.
[0085] Example 8 The difference from Example 1 is that 0.5 g of polyvinyl alcohol is used in step (1), and the rest is the same as Example 1.
[0086] Example 9 The difference from Example 1 is that 1 g of polyvinyl alcohol is used in step (1), and the rest is the same as Example 1.
[0087] Example 10 The difference from Example 1 is that 5 g of polyvinyl alcohol is used in step (1), and the rest is the same as Example 1.
[0088] Embodiment 11 The difference from Example 1 is that 6 g of polyvinyl alcohol is used in step (1), and the rest is the same as Example 1.
[0089] Example 12 The difference from Example 1 is that the reaction in step (1) is carried out at 50° C. for 6 h. The rest is the same as Example 1.
[0090] Example 13 The difference from Example 1 is that the reaction in step (1) is carried out at 150° C. for 1 h. The rest is the same as Example 1.
[0091] Embodiment 14 The difference from Example 1 is that the curing treatment is performed at 500° C. for 8 h in step (2). The rest is the same as Example 1.
[0092] Embodiment 15 The difference from Example 1 is that in step (2), the curing treatment is performed at 800° C. for 1 h. The rest is the same as Example 1.
[0093] Example 16 The difference from Example 1 is that the activation treatment is performed at 1100° C. for 300 min in step (2). The rest is the same as Example 1.
[0094] Embodiment 17 The difference from Example 1 is that in step (2), the activation treatment is performed at 1400° C. for 30 min. The rest is the same as Example 1.
[0095] Embodiment 18 The difference from Example 1 is that in step (3), the temperature of lithium deposition is 300° C. and the evaporation time is 5 min. The other steps are the same as Example 1.
[0096] Embodiment 19 The difference from Example 1 is that in step (3), the temperature of lithium deposition is 400° C. and the evaporation time is 25 min. The other steps are the same as Example 1.
[0097] Embodiment 20 The difference from Example 1 is that the amount of lithium used in step (3) is 0.5 g, and the rest is the same as Example 1.
[0098] Embodiment 21 The difference from Example 1 is that the amount of lithium used in step (3) is 1 g, and the rest is the same as Example 1.
[0099] Embodiment 22 The difference from Example 1 is that the amount of lithium used in step (3) is 5 g, and the rest is the same as Example 1.
[0100] Embodiment 23 The difference from Example 1 is that in step (3), the amount of lithium used in step (3) is 6 g, and the rest is the same as Example 1.
[0101] Comparative Example 1 The difference from Example 1 is that carboxylated carbon nanotubes and polyvinyl alcohol are not added in step (1), and the rest is the same as Example 1.
[0102] Comparative Example 2 The difference from Example 1 is that step (3) is not performed, that is, the carbon nanotube-doped porous carbon in step (2) is used as the negative electrode material.
[0103] Performance Testing 1. Scanning electron microscope (SEM) test: Figure 1 This is a SEM image of lithium carbon nanotube-doped porous carbon prepared in Example 1. Figure 1 It can be seen that the material presents a small-diameter spherical structure with uniform size distribution and a small amount of carbon nanotubes entangled. The particle size of the material is between 5-15μm.
[0104] 2. Physical and chemical properties and button battery test: 2.1 Physical and chemical performance test: The pore volume and pore size of the porous carbon obtained in Examples 1-11 and Comparative Examples 1-2 were tested with reference to the national standard GB / T-38949-2020 "Standard particle method for determination of pore size of porous membranes"; and the specific surface area and tap density were tested in accordance with the national standard GB / T-24533-2019 "Graphite, a graphite negative electrode material for lithium-ion batteries"; and the powder conductivity of each porous carbon material was tested using a four-probe tester; the test results are shown in Table 1 below.
[0105] 2.2 Button battery performance test: The porous carbon corresponding to Examples 1-23 and Comparative Examples 1-2 was used as the negative electrode material for lithium-ion batteries to prepare button batteries according to the following method: A binder, a conductive agent and a solvent are added to each corresponding porous carbon composite material, stirred to make a slurry, coated on a copper foil, and dried and rolled to obtain a negative electrode sheet; the binder used is LA132, the conductive agent is SP (conductive carbon black), and the solvent is NMP (N-methylpyrrolidone), and the usage ratio of the composite material, SP, LA132, and NMP is 80g:15g:15g:300mL; the electrolyte is a solution with LiPF6 as the electrolyte, and the concentration is 1mol / L, wherein the solvent is a mixture of EC and DEC in a volume ratio of 1:1; the metal lithium sheet is the counter electrode, and the diaphragm is a polypropylene (PP) film.
[0106] Each button cell was assembled in an argon-filled glove box and then subjected to the following performance tests: Electrochemical performance test: The electrochemical performance was tested on a Wuhan Blue Electric CT2001A battery tester, with a charge and discharge voltage range of 0.005V to 2.0V and a charge and discharge rate of 0.1C. The discharge capacity and initial efficiency of the corresponding button cell were tested. At the same time, the rate performance (1C / 0.1C) and cycle performance (0.1C / 0.1C, 100 weeks) of the corresponding button cell were tested. The test results are shown in Table 1.
[0107] Table 1 Test results of Examples 1-23 and Comparative Examples 1-2
[0108] The applicant declares that the present invention illustrates the process method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned process steps, that is, it does not mean that the present invention must rely on the above-mentioned process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing lithium carbon nanotube-doped porous carbon, characterized in that: The preparation method comprises: Firstly, a carbon nanotube-doped resin precursor is prepared by a coprecipitation method, and then a curing treatment is performed to obtain a carbon nanotube-doped resin; Then, the carbon nanotube-doped resin is activated by using carbon dioxide to obtain carbon nanotube-doped porous carbon; Then, lithium is deposited on the carbon nanotube-doped porous carbon by using a vacuum evaporation method to obtain lithium carbon nanotube-doped porous carbon.
2. The preparation method according to claim 1, characterized in that The method for preparing a carbon nanotube-doped resin precursor by a coprecipitation method comprises: First, add an aqueous solution of phenolic compounds, then drop an aqueous solution of aldehyde compounds, and then add carbon nanotubes, pore-forming agent and ammonia water in sequence, mix well, react at 50-100° C. for 1-6 hours, and filter to obtain a carbon nanotube-doped resin precursor.
3. The preparation method according to claim 2, characterized in that: The mass ratio of the phenolic compound, the aldehyde compound, the carbon nanotube and the pore-forming agent is 100:100-200:1-5:1-5.
4. The preparation method according to claim 2, characterized in that: The carbon nanotubes include one or more of hydroxylated carbon nanotubes, aminated carbon nanotubes, carboxylated carbon nanotubes or nitrogen-doped carbon nanotubes; The phenolic compound includes one or more of m-cresol, p-cresol, o-cresol, 3,5-dimethylphenol or resorcinol; The aldehyde compound includes one or more of formaldehyde, acetaldehyde, furfural or salicylaldehyde; The pore-forming agent includes one or more of polyvinyl alcohol, polyvinyl pyrrolidone or polyvinyl amine.
5. The preparation method according to claim 1, characterized in that: The method for curing the carbon nanotube-doped resin precursor comprises: The carbon nanotube-doped resin precursor is cured at 500-800° C. for 1-6 hours to obtain the carbon nanotube-doped resin.
6. The preparation method according to claim 1, characterized in that: The method for activating the carbon nanotube-doped resin comprises: After heating the carbon nanotube-doped resin to 1100-1400° C., introducing carbon dioxide and performing activation treatment for 30-300 minutes to obtain carbon nanotube-doped porous carbon; The flow rate of carbon dioxide for activation treatment is 100-500 ml / min.
7. The preparation method according to any one of claims 1 to 6, characterized in that: The method for depositing lithium on the carbon nanotube-doped porous carbon using a vacuum evaporation method comprises: Lithium deposition is carried out under vacuum conditions. First, a high-energy laser beam is used to irradiate the lithium, which is then vaporized and deposited into the pores and surface of the carbon nanotube-doped porous carbon. The evaporation time is 5-15 minutes, and then carbon dioxide is introduced for passivation treatment.
8. The preparation method according to claim 7, characterized in that: The mass ratio of carbon nanotube-doped porous carbon to lithium is 100:1-5; The wavelength of the laser beam is 900-1090nm, the pulse width is 0.5ms-4ms, and the laser power is 100W-600W; The flow rate of carbon dioxide for passivation treatment is 100-500ml / min; The passivation treatment time is 30-300min.
9. A lithium carbon nanotube-doped porous carbon obtained by the preparation method according to any one of claims 1 to 8, characterized in that: The lithium carbon nanotube-doped porous carbon comprises 1-5wt% carbon nanotubes, 1-5wt% lithium carbonate and 90-98wt% porous carbon.
10. Use of the lithium carbon nanotube-doped porous carbon as claimed in claim 9 in preparing a secondary battery.
Citation Information
Patent Citations
Metal-doped porous carbon and silicon carbon material and preparation method thereof
CN118419892A
Carbon material for negative electrode of lithium secondary battery, method for producing the same, negative electrode of lithium secondary battery and lithium secondary battery
CN102017246A
Nitrogen and phosphor co-doped porous carbon nanotube, and preparation method and application thereof
CN105006375A
Lithium metal composite material, modified material thereof, preparation methods of lithium metal composite material and modified material, and battery
CN114824218A
Lithium metal composite material and modified material thereof, and preparation methods and applications of lithium metal composite material and modified material
CN114944470A
Cited By
Porous carbon composite material and preparation method thereof
CN120646829A
